2020
DOI: 10.1136/bmjqs-2019-010260
|View full text |Cite
|
Sign up to set email alerts
|

Cautionary study on the effects of pay for performance on quality of care: a pilot randomised controlled trial using standardised patients

Abstract: BackgroundDue to the difficulty of studying incentives in practice, there is limited empirical evidence of the full-impact pay-for-performance (P4P) incentive systems.ObjectiveTo evaluate the impact of P4P in a controlled, simulated environment.DesignWe employed a simulation-based randomised controlled trial with three standardised patients to assess advanced practice providers’ performance. Each patient reflected one of the following: (A) indicated for P4P screenings, (B) too young for P4P screenings, or (C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Therefore, due to these issues coupled with COVID-19–related cancer screening cancelations and delays [ 21 ], health care professionals’ performance in value-based contracts are at risk [ 53 ]. One consequence could be decreased screening rates and the resulting poor performance in cancer screening metrics, which in turn can lead to decreased quality incentives [ 54 , 55 ].…”
Section: Cancer Screening Challenges Opportunities and Solutionsmentioning
confidence: 99%
“…Therefore, due to these issues coupled with COVID-19–related cancer screening cancelations and delays [ 21 ], health care professionals’ performance in value-based contracts are at risk [ 53 ]. One consequence could be decreased screening rates and the resulting poor performance in cancer screening metrics, which in turn can lead to decreased quality incentives [ 54 , 55 ].…”
Section: Cancer Screening Challenges Opportunities and Solutionsmentioning
confidence: 99%
“…As evidence of the rich data derived from simulation-based studies, a pilot simulation evaluation of pay-for-performance (P4P) incentives revealed a tendency for health care providers in a primary care setting to divert resources from unrewarded (unmeasured) tasks to rewarded (measured) tasks. 10 The study used a simulation-based RCT to assess the impact of P4P incentives on clinical behavior. Thirty-five primary care providers were recruited to provide patient evaluations for the same 3 simulated patients and were randomized into 1 of 2 study arms: a control or a P4P incentive.…”
mentioning
confidence: 99%
“…As evidence of the rich data derived from simulation-based studies, a pilot simulation evaluation of pay-for-performance (P4P) incentives revealed a tendency for health care providers in a primary care setting to divert resources from unrewarded (unmeasured) tasks to rewarded (measured) tasks 10 . The study used a simulation-based RCT to assess the impact of P4P incentives on clinical behavior.…”
mentioning
confidence: 99%